SIRT4 enhances the sensitivity of ER‐positive breast cancer to tamoxifen by inhibiting the IL‐6/STAT3 signal pathway. (1st October 2019) - Xing, Jilin; Li, Ji; Fu, Lin; Gai, Junda; Guan, Jingqian; Li, Qingchang
Abstract: Recent advances in endocrine therapy have improved the prospects for estrogen receptor‐positive breast cancer. Tamoxifen is an effective drug for patients with estrogen receptor‐positive breast cancer, but the development of resistance is common. Therefore, discovering ways to enhance the sensitivity of cancer cells to tamoxifen may help improve breast cancer treatment. We studied the biological role of sirtuin 4 (SIRT4) in tamoxifen‐treated MCF7 and T47D cells. The levels of the MYC proto‐oncogene (MYC) and cyclin D1 (CCND1) were detected by western blotting and quantitative reverse transcription‐polymerase chain reaction in breast cancer cells with SIRT4 overexpression or depletion. Immunofluorescence and western blotting were used to assess the phosphorylation status of signal transducer and activator of transcription 3 (STAT3). SIRT4 overexpression decreased the half maximal inhibitory concentration of tamoxifen in MCF7 and T47D cells, while its depletion increased it. Thus, SIRT4 enhances the sensitivity of breast cancer cells to tamoxifen. Moreover, western blotting revealed decreased STAT3 phosphorylation after SIRT4 transfection. The transcription and translation of MYC and CCND1, target genes of the STAT3 pathway, were also blocked. Immunofluorescence revealed that pathway activation and nuclear STAT4 translocation were suppressed when SIRT4 was overexpressed. Furthermore, the effects of SIRT4 overexpression or depletion on proliferation could be offset by STAT3 activation or inhibition. Taken together, these results demonstrate that SIRT4 enhances the tamoxifen sensitivity of breast cancer cells by inhibiting the STAT3 signaling pathway. With this knowledge, therapeutic strategies with reduced drug resistance risk may be developed. Abstract : We proved for the first time that SIRT4 enhances sensitivity of breast cancer cells to tamoxifen. Western blotting showed that p‐STAT3 levels were reduced after SIRT4 transfection and that transcription and translation of MYC and CCND1 were blocked. Immunofluorescence revealed that STAT3 activation and nuclear translocation were suppressed when SIRT4 was overexpressed.